(untitled) (Journal of Universal Science Research, 2024)
In the course of this research, the features of teaching biology using modern methods were analyzed. The methodology of teaching biology as a pedagogical science is inextricably linked with didactics. Based on the unique characteristics of school biology, the methodology of teaching biology develops theoretical and practical problems of the content, forms, methods and tools of education and training. based on features. It is necessary to cover the ways of turning the student into a subject of a full-fledged learning process in biology lessons.